FORMATION AND PREPROCESSING OF MRI AND CT IMAGE DATASETS FOR BRAIN TUMORS - Mukhamediyeva , Dildora; Abdirakhimov, Amriddin (Techscience uz - Topical Issues of Technical Sciences, 2025)
This article examines the crucial role of Magnetic Resonance Imaging (MRI) and Computed Tomography (CT) scans in the diagnosis and classification of brain tumors. From a scientific perspective, the study investigates the processes of compiling MRI and CT brain image datasets, their analysis, development, and preparation for deep learning models.